Flexural Performance of Concrete with Modified Eucalyptus Bark Waste as Partial Replacement of Fine Aggregate - Azzan Farizi; Anis Aulia Ulfa; Fatmawati Fatmawati (Civil Engineering Dept, Balikpapan State Polytechnics, 2025)
The utilization of eucalyptus bark waste as an alternative material in concrete represents an effort to reduce by-products from the forestry industry. However, the organic nature of this material may influence the mechanical performance of concrete. This study investigates the effect of alkali-treated eucalyptus bark waste used as a partial replacement for fine aggregate on the flexural strength of concrete. Prior to mixing, the bark waste was modified through alkaline treatment using a 1% NaOH solution for approximately 24 hours to improve its compatibility with the cement matrix. Replacement levels of 0%, 1%, 2.5%, and 5% by weight of fine aggregate were examined. Concrete beam specimens were tested for flexural strength at 28 days. The results indicate that increasing the proportion of eucalyptus bark waste leads to a reduction in flexural strength. The control mixture (0%) satisfies the flexural strength requirement of K250 concrete based on SNI T-15-1991-03, whereas mixtures containing eucalyptus bark waste fail to meet the minimum criterion. These findings suggest that alkali-treated eucalyptus bark waste is not suitable as a fine aggregate substitute in structural concrete.